Anatomical Research on the Subacromial Interval Following Implantation of Clavicle Hook Plates - Deng, Z.; Cai, L.; Ping, A.; Ai, Q.; Wang, Y. (International Journal of Sports Medicine, 2014)
This article aimed to explore whether hook plate implantation significantly narrowed the subacromial space. 24 shoulder joints were implanted with clavicle hook plates. A Vernier caliper was used to measure the length and thickness of the acromion. In addition, the length and thickness of the hook of the plate were measured. The data from all measurements recorded were divided into 2 groups Group A, the length group: the length of acromion and the hook, and Group B, the thickness group: the thickness of acromion and the depth of hook. There are significant statistical differences when comparing between the subgroups within each group. The depth of the hook exceeds the thickness of the acromion (12.41±2.80 mm vs. 10.44±2.59 mm, respectively), the hook plate implantation significantly narrowed the subacromial space by 1.97±1.19 mm (p<0.01), and the length of the hook was shorter than that of the acromion by 9.75±3.64 mm (p<0.01). Our findings revealed that the hook plate with only 3 depths could not match the acromion satisfactorily and the hook plate implantation significantly narrowed the subacromial space. A hook plate with a variable depth, which can match better with patient’s anatomy, is worthy of further investigation in the future.
Keywords: clavicle hook plate; subacromial impingement syndrome; anatomic research